PENGARUH PERILAKU KONSUMEN TERHADAP MINAT BELANJA ONLINE SHOP - Baitipur, Mardiana Nisa; Pujiastuti, Endah; Annisa, Qiki (Journal Accounting International Mount Hope, 2024)
This study aims to determine the influence of consumer behavior on online shop shopping intentions among Politeknik Stibisnis Tegal students. The data analysis method used in this research is quantitative where in this method the researcher collects data using a questionnaire which are distributed to the study population, namely all 224 students of the Politeknik Stibisnis Tegal with a total sample of 145 students, then the results are tested using a validity test, test reliability, classical assumption test, simple linear regression test and hypothesis testing using the SPSS version 21.0 program.The results showed that from the t test (partial) it was obtained that the value of t count > t table was 10.257 > 1.976 with a significance value of 0.000 > 0.05. So it can be concluded that consumer behavior (X) has a positive effect on online shop shopping interest (Y) for Politeknik Stibisnis Tegal students to shop online shops.